Analyzing the Perceptions of Students, Lecturers, and Staff in Understanding the Buddhist Motto: Excellence and Character in Higher Education Management - Syah, Rahmat; Budiwinarto, Arif; Bariboon, Gumpanat (Universitas Negeri Semarang, 2024)
This study aims to explore the perceptions and understandings of students, lecturers, and staff about the meaning of the